Factors related to risky alcohol consumption and binge drinking in Spanish college students: a cross-sectional study - Enrique Ramón-Arbués; Isabel Antón-Solanas; Isabel Rosario Blázquez-Ornat; Piedad Gómez-Torres; Loreto García-Moyano; Eva Benito-Ruiz (BMJ Open)
Objectives The aim of this study was to determine the prevalence of risky alcohol consumption and regular binge drinking, and their associated factors, in Spanish college students.Design A cross-sectional study was conducted.Setting This study took place at a private university in a northern region of Spain.Participants A total of 330 Spanish undergraduate university students enrolled in the 2022–2023 academic year voluntarily agreed to participate in this investigation.Primary and secondary outcome measures Data collection included sociodemographic information and health-related behaviours. The Alcohol Use Disorders Identification Test was used to assess alcohol consumption. Logistic regression models were used to identify independent predictors for risky alcohol consumption and regular binge drinking.Results 40.0% of participants reported risky alcohol consumption, and 26.7% were classified as regular binge drinkers. Factors associated with risky alcohol consumption included smoking (OR=3.54, 95% CI 2.03 to 6.14) and problematic internet use (OR=2.10, 95% CI 1.24 to 3.53). Conversely, being older than 30 years was associated with a lower likelihood (OR=0.22, 95% CI 0.08 to 0.60). Regular binge drinking was associated with living outside the family home (OR=2.78, 95% CI 1.56 to 4.95), smoking (OR=3.53, 95% CI 1.94 to 6.40) and problematic internet use (OR=2.19, 95% CI 1.23 to 3.89). In contrast, being female (OR=0.50, 95% CI 0.27 to 0.94) and being over 30 years old (OR=0.28, 95% CI 0.10 to 0.86) were inversely associated.Conclusions Risky alcohol consumption and binge drinking are relatively common among Spanish university students. Interventions to promote responsible alcohol consumption among this population should be implemented in collaboration with other stakeholders.